2000
DOI: 10.1034/j.1600-0536.2000.042001005.x
|View full text |Cite
|
Sign up to set email alerts
|

Metals and arsenic in eye shadows

Abstract: The regulations relating to cosmetic products give no limit values for toxic elements such as metals or arsenic occurring as impurities in cosmetic products. The present study of metals (lead, cobalt, nickel, chromium) and arsenic in eye shadows in 88 colors of 25 brands and 49 products provides a basis for assessing the safety of eye shadow. 66 out of 88 (75%) of the colors contained more than 5 ppm of at least one of the elements, and all 49 products contained more than one 1 ppm of at least 1 of the element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
123
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 14 publications
(17 reference statements)
5
123
1
3
Order By: Relevance
“…Leather products have now become the most important known source of chromium exposure in Denmark and chromium allergy has primarily become a consumer problem (7). Other consumer products with a risk of causing chromium dermatitis, although more theoretically than practically, are cleaning products and make-up (8)(9)(10).…”
mentioning
confidence: 99%
“…Leather products have now become the most important known source of chromium exposure in Denmark and chromium allergy has primarily become a consumer problem (7). Other consumer products with a risk of causing chromium dermatitis, although more theoretically than practically, are cleaning products and make-up (8)(9)(10).…”
mentioning
confidence: 99%
“…Lipstick can become contaminated with lead via the use of contaminated raw materials or via the use of pigments that contain lead. The level of lead was less than 20 ppm in all products in a study on its presence in 88 different colours of eye shadow [9].Cadmium is present in many cosmetics products but mostly present in lipsticks and face powders. Its color is deep yellow to orange.…”
Section: Introductionmentioning
confidence: 91%
“…With many new products released into the market every season, it is hard to keep track of the safety of every pro-duct and some products may carry carcinogenic contaminant [4].Many cosmetic products contain heavy metals such as lead, arsenic, mercury, cobalt, and nickel as ingredients or impurities. Recent research has reported that these metals can easily cause many types of skin problems [5,6].The use of some heavy metals in cosmetic has been controversial due to the biological accumulation of those metals and their toxicity in the human body. In most countries, it is legally prohibited to use lead, arsenic, and mercury in skin cosmetic products for example; lead is prohibited as part of cosmetic compositions in Korea, the European Union, and China.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the preservative thiomersal (mercury), the progressive hair dye lead acetate and a number of tattoo pigments such as red cinnabar mercuric sulfide, Since the issue of heavy metals as deliberate cosmetic ingredients have been addressed, attention is turned to the presence of these substances as impurities. The metals of primary toxicological concern in cosmetics are lead, arsenic, cadmium, mercury and antimony [12]. Dermal exposure is expected to be the most significant route for cosmetic products since the majority of cosmetics are applied to the skin.…”
Section: Introductionmentioning
confidence: 99%